Budidaya Selada pada Vertikultur Hidroponik Sistem Karpet - Pamungkas, Hanggoro Sabdo; Putri, Retno Bandriyati Arni; Muliawati, Endang Setia (Agrosains : Jurnal Penelitian Agronomi, 2013)
The limitation of land area that for fulfillment of food savety needs to be resolved immediately. One of the things that can be done, is the use technology of verticulture system without soil media. Pouch system use the carpet is one verticulture system that can be applied. Basically, carpet is capable of holding water and has a high capillarity, so it can be used as a media pit as conductor of nutrients to the substrat medium. This study aimed to evaluate the hydroponic verticulture of carpet system on lettuce cultivation. This study was conducted in August 2013 to October 2013 at the Greenhouse B, Faculty of Agriculture, University of Sebelas Maret Surakarta. The treatments was arranged based on the completely randomized design (CRD) used factorial with 2 factor consists of 4 level and one control. Each treatment was repeated 3 times. Based on the efficiency use of nutrients and electric cost, the result showed that vertical cross pattern and 15 minutes fertigation treatments gave best results.